Gender and Sexualities in the Interamerican Journal of Psychology: a systematic review - Souza, Beatriz; Tiago, Eliana; Mongim, Jocilene; Lindinger, Luciana; Barone, Antonella (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
This systematic review on sexualities and gender covers 80 articles, published by the Interamerican Journal of Psychology until the year 2019. The sample, selected and classified into three themes by the thematic analysis method, shows a productivity raise in this regard upon the 1990s. Ever since, debates on sexual differences and roles amidst the sample have declined while productions on gender have grown, according to the first theme. On the second, it was possible to infer that such an increase had significant collaboration from the health areas, highlighting yet the importance of some health, sexual and (non-)reproductive health intervention strategies. The contribution of family arrangements and motherhood was pointed out in the third theme along with the lack of studies that are not only centered in cis-heteronormativity. Therefore, we outline our snippet from a genealogical perspective in Latin American Psychology, highlighting the importance to think of and to implement strategies that are closer to the psychosocial, ethical and cultural realities of the region.